Clinical characteristics and management of olecranon and prepatellar septic bursitis in a multicentre study. (22nd July 2021) - Charret, Laurie; Bart, Géraldine; Hoppe, Emmanuel; Dernis, Emmanuelle; Cormier, Grégoire; Boutoille, David; Le Goff, Benoit; Darrieutort-Laffite, Christelle
Abstract: Background: No current guidelines are available for managing septic bursitis (SB). Objectives: To describe the clinical characteristics and management of olecranon and prepatellar SB in five French tertiary care centres. Methods: This is a retrospective observational multicentre study. SB was diagnosed on the basis of positive cultures of bursal aspirate. In the absence of positive bursal fluid, the diagnosis came from typical clinical presentation, exclusion of other causes of bursitis and favourable response to antibiotic therapy. Results: We included 272 patients (median age of 53 years, 85.3% male and 22.8% with at least one comorbidity). A microorganism was identified in 184 patients (67.6%), from bursal fluids in all but 4. We identified staphylococci in 135 samples (73.4%), streptococci in 35 (19%) and 10 (5.5%) were polymicrobial, while 43/223 bursal samples remained sterile (19.3%). Forty-nine patients (18%) were managed without bursal fluid analysis. Antibiotic treatment was initially administered IV in 41% and this route was preferred in case of fever ( P = 0.003) or extensive cellulitis ( P = 0.002). Seventy-one (26%) patients were treated surgically. A low failure rate was observed ( n = 16/272, 5.9%) and failures were more frequent when the antibiotic therapy lasted <14 days ( P = 0.02) in both surgically and medically treated patients. Conclusions: Despite variable treatments, SB resolved in the majority of cases even when the treatment was exclusively medical. The success rate was equivalent in the non-surgical and the surgical management groups. However, a treatment duration of <14 days may require special attention in both groups.